The mediating effect of brand image on the relationship between E-WOM and purchase intention: the case study of FOREO skin-care devices - Cuong Nguyen; Sam Pham; Ly Nguyen (Cogent Business & Management)
Electronic Word of Mouth (eWOM) is increasingly prominent in marketing communication tools. Online buyers tend to research more on the product before deciding to purchase. This paper examines the mediating effect of eWOM on FOREO skin-care device purchase intention in Vietnam, focusing on the mediating role of brand image. SPSS 26 and AMOS 24 software were utilized to process online survey data from 412 respondents. The findings demonstrated that eWOM credibility, quantity, and quality positively affected brand image. Credibility is the most important factor, followed by quality and quantity. The study also indicated that brand image mediates between country-of-origin image and purchase intention. Despite the limitations, the author has proposed the significance of the role of practical management in this research as well as recommendations for future studies.